Pratique d’Interdits Alimentaires: Entre Logique Identitaire, Enjeux Sanitaires Et Conservation De La Biodiversité Chez Les Agni De Bongouanou (Côte d’Ivoire) - Valentin, Koné Bognan; Gilbert, Fokou; Bouaki, Kouadio Baya; Obrist, Brigit; Gnabeli, Roch Yao; Bonfoh, Bassirou (European Scientific Journal, ESJ, 2018)
Social norms are depriving Agni communities of Bongouanou in central-eastern Côte d’Ivoire of certain foods adding to a state of food insecurity. Based on significant cases of food restrictions, this study analyzed nutritional practices that position individuals and groups in social normative frameworks. This work focused on institutional frameworks where health and food taboo aspects were most shared. This study aims to analyze the social imaginaries associated with food restriction and their link to health in a context of food insecurity. More particularly, it aims at exploring beliefs and representations associated with health risks due to food restrictions. Based on a qualitative approach using data collection techniques as direct observation, semi-structured interviews and focus group discussions, this study was conducted in four villages where the consumption of catfish by local populations is totally prohibited. Social identity theory and the cultural materialism perspective were used for analysis and interpretation of knowledge and beliefs associated with food restrictions. The non-consumption of catfish from the Socotè Lake participated to sociability and the preservation of the indigenous "Agni of Bongouanou" identity. Additionally, food restrictions are determinants of physical and reproductive health of members of the social group. In fact, the collective imaginary of Agni from Bongouanou establishes a causal link between the consumption of this restricted food and health problems. Finally, it has emerged that this food practice could impact the cultural well-being of the community while contributing to the conservation of biodiversity.